Gauging the Impact of FISMA on Software Security. - Gandhi, Robin A.; Crosby, Keesha; Siy, Harvey; Mandal, Sayonnha (Computer (00189162), 2014)
A newly developed instrument provides sophisticated content analysis to help determine the relevance for software security of the National Institute of Standards and Technology's FISMA-mandated security controls.